2005
DOI: 10.1039/b504631a
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting isolobal relationships to create new ionic liquids: novel room-temperature ionic liquids based upon (N-alkylimidazole)(amine)BH2+“boronium” ions

Abstract: Readily prepared imidazole-based boronium ions form stable, hydrophobic, room-temperature ionic liquids (RTIL) with unique electronic and spectroscopic characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 27 publications
(6 reference statements)
1
25
0
Order By: Relevance
“…As in the case of EMBzImTFSI, the Me 3 NBH 2 MImTFSI (Me 3 NBH 2 MIm = (N-methylimidazole) (trimethylamine)boronium) contains disordered TFSI anions in the trans-conformation and only weak intermolecular contacts in the lattice [54]. This is the first structural model of (N-alkylimidazole)(amine)boronium-based ionic liquids.…”
Section: Fluorocomplex Saltsmentioning
confidence: 88%
“…As in the case of EMBzImTFSI, the Me 3 NBH 2 MImTFSI (Me 3 NBH 2 MIm = (N-methylimidazole) (trimethylamine)boronium) contains disordered TFSI anions in the trans-conformation and only weak intermolecular contacts in the lattice [54]. This is the first structural model of (N-alkylimidazole)(amine)boronium-based ionic liquids.…”
Section: Fluorocomplex Saltsmentioning
confidence: 88%
“…The ILs bearing a perfluoroalkyltrifluoroborates [8] were also reported by Tatsumi et al Watanabe et al reported lithium cation containing organoborate ILs bearing oligoethers [9]. ILs including a boronium cation were also reported by Rogers and coworkers [10].…”
Section: Introductionmentioning
confidence: 76%
“…The bulky {[HB(MesImH) 3 ]Br 2 } (2), and tris(tert-butyl-imidazol-3-ium-1-yl)hydroborate, {[HB(t-BuImH) 3 ]Br 2 } (3), were synthesized by a similar synthetic path to that reported for the preparation of ionic liquid imidazole-based ''boronium" ions [51]. Three equivalents of 1-tert-butylimidazole or 1-mesityl-imidazole were heated in refluxing dichloromethane with (CH 3 ) 2 S:BHBr 2 (Scheme 2).…”
Section: Synthesesmentioning
confidence: 99%